Transforming Islamic Education through IT: Insights from Da'wah Practices in South Korea - Ulumudin, Ihya; Basyiroh, Iis; Ramdani, Cepi (International Journal of Education and Digital Learning (IJEDL), 2024)
This article explores the transformative impact of Information Technology (IT) on Islamic education through insights gained from da'wah practices in South Korea. The integration of IT tools such as mobile applications, online courses, and social media platforms has revolutionized traditional methods of religious instruction, enhancing accessibility, engagement, and community building within the Muslim minority context. Drawing on qualitative research methods including interviews and case studies, this study examines the adoption of IT in Islamic educational initiatives, identifies challenges and opportunities, and discusses future trends such as virtual reality (VR) and augmented reality (AR) in religious education. The findings underscore the potential of IT to facilitate inclusive and dynamic educational practices while addressing socio-cultural and ethical considerations in an increasingly digital era.